2020
DOI: 10.20944/preprints202004.0540.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is Happening with Smokers and COVID-19? A Systematic Review and a Meta-Analysis

Abstract: SARS-CoV-2 is a new coronavirus that has caused a worldwide pandemic. It produces severe acute respiratory disease (COVID-19), which is fatal in many cases, characterised by cytokine release syndrome (CRS). According to the World Health Organization (WHO), those who smoke are likely to be more vulnerable to infection. Here, in order to clarify the epidemiologic relationship between smoking and COVID-19, we present a systematic literature review until 28 April 2020 and a meta-analysis. It includes 18 recent COV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…A systematic review conducted by Rubio et al demonstrated that the proportion of smokers among COVID-19 patients is signi cantly lower than the percentage of smokers among general population in three different countries including China, Italy and the USA. Thus, they postulated that smokers are signi cantly less likely to develop severe disease and be hospitalized (16). The proposed mechanism is that nicotine can alleviate the ongoing in ammatory responses and cytokine storm in COVID-19 patients through the cholinergic anti-in ammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review conducted by Rubio et al demonstrated that the proportion of smokers among COVID-19 patients is signi cantly lower than the percentage of smokers among general population in three different countries including China, Italy and the USA. Thus, they postulated that smokers are signi cantly less likely to develop severe disease and be hospitalized (16). The proposed mechanism is that nicotine can alleviate the ongoing in ammatory responses and cytokine storm in COVID-19 patients through the cholinergic anti-in ammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that smoking makes individuals more susceptible to COVID-19 and results in higher risk of severe disease and ICU admission (11,(13)(14)(15). Whereas, some studies implicate that not only smoking does not cause harm but also can have a protective role for patients with COVID-19, due to anti-in ammatory effects of nicotine (6,16,17). Therefore, the exact in uence of smoking on patients with COVID-19 still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The authors thank Isabel Najera, Jose Antonio Najera, and Julio Basulto for helpful comments that greatly improved the manuscript. This manuscript was released as Pre-print at https://www.preprints.org/ manuscript/202004.0540/v1 on 2020/04/30 that has not been peer-reviewed [92].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, a systematic review and meta-analysis published recently claims that the findings of 18 recent COVID-19 clinical and epidemiological studies show that smokers were statistically less likely to be hospitalized (OR=0.18, 95%CI: 0.14-0.23, p<0.01) [ 7 ]. Thus, the authors state: “The number of hospitalized smokers was smaller than expected based on the smoking prevalence in the different countries.…”
Section: Introductionmentioning
confidence: 99%